2010
DOI: 10.1080/14733140903337292
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based problem‐solving therapy in self‐poisoning females: A pilot study

Abstract: Aims: The treatment of suicidal behaviour remains limited in efficacy. This pilot study assessed the effectiveness of a time‐limited, group‐based problem‐solving therapy intervention compared with a treatment as usual control group, in females who self‐poison. Method: A total of 18 clients were equally randomised to treatment or control groups. All clients were assessed using standardised questionnaires for depression, hopelessness, suicidal ideation and social problem‐solving skills, at pre‐treatment, post‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…We classified the 28 trials (Additional file 1: Table S1) into four categories by intervention type: active contact and follow-up interventions (Table 1) (18 publications from 14 trials) [21, 24, 25, 2730, 33, 3741, 44, 45, 5052], psychotherapy (12 publications from 10 trials) [22, 26, 32, 3436, 42, 43, 4648, 54], pharmacotherapy (1 publication from 1 trial) [23], and miscellaneous interventions (3 publications from 3 trials) [31, 49, 53]. Fourteen trials in 18 publications were active contact and follow-up interventions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We classified the 28 trials (Additional file 1: Table S1) into four categories by intervention type: active contact and follow-up interventions (Table 1) (18 publications from 14 trials) [21, 24, 25, 2730, 33, 3741, 44, 45, 5052], psychotherapy (12 publications from 10 trials) [22, 26, 32, 3436, 42, 43, 4648, 54], pharmacotherapy (1 publication from 1 trial) [23], and miscellaneous interventions (3 publications from 3 trials) [31, 49, 53]. Fourteen trials in 18 publications were active contact and follow-up interventions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A description of trial characteristics is shown in online supplementary table S3 . The majority of trials that provided data for the primary outcome (n=19) 41 42 48 52 55 56 60–62 65 67 69–72 74 75 77 78 87 were medium (80–280 participants), eight were small (<80 participants) 38 44 47 49 50 58 81 82 and nine were large (>280 participants). 39 40 43 54 57 59 63 68 79 Of the remaining trials that did not contribute data to the primary outcome, five trials were small, 45 46 64 73 80 three were medium; 51 53 76 and one was large.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty trials used TAU, and six used TAU+ as the comparator. 38 43 48 54 58 63 Seven trials used an alternative controlled intervention, 44 45 50 61 74–76 one trial 64 used a waitlist control comparison condition and one trial 69 used a no-intervention control comparison group (see online supplementary table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this meta-analysis did not directly examine the effects of these treatments on reduction of actual DSH. A recent study of group-based Problem-Solving Therapy for adult females who engaged in self-poisoning also found preliminary evidence for improvement with depression, hopelessness, suicidal ideation, and social problem solving, but also failed to show a significant difference between the control and treatment group; indeed, neither group evidenced DSH during the two-month follow-up [20]. …”
Section: Introductionmentioning
confidence: 99%